Comparative Institutional Advantage in the European Sovereign Debt Crisis - Alison Johnston; Bob Hancké; Suman Pant (London School of Economics and Political Science (LSE), European Institute, 2013)
Excessive fiscal spending is commonly cited as a primary cause of the current European sovereign debt crisis. We develop an alternative hypothesis which better accounts for systemic differences towards EMU countries' exposure to market speculation: the rise of competitiveness imbalances which contributed to national imbalances in total borrowing. We outline that one driver of competitiveness divergence is a country's capacity to limit sheltered sector wage growth, relative to wage growth in the manufacturing sector. We posit that corporatist institutions which linked sectoral wage developments together in the surplus countries provided them with a comparative wage advantage vis-à-vis EMU's debtor nations, explaining why the EMU core has emerged relatively unscathed from market speculation during the crisis despite that fact that some of these countries had poor fiscal performances during EMU's early years. Using a panel regression analysis, we demonstrate that rising differentials between public and manufacturing sector wage growth, as well as wage governance institutions which weakly coordinate exposed and sheltered sectors, are significantly correlated with export decline. We also find that weak governance institutions are significantly associated with more prominent export decline inside a monetary union, compared to outside of monetary union.
Keywords: 330; European Monetary Union; European Debt Crisis; Corporatism; Sectoral Wage Bargaining